2019
DOI: 10.17479/jacs.2019.9.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Intestinal Obstruction from Phytobezoar

Abstract: Purpose: Phytobezoar is the most common type of bezoar, which can occasionally present as an intestinal obstruction. In this study, the surgical experience and outcome in the management of intestinal obstruction caused by bezoars are described. Methods: A retrospective analysis of all operative cases of bezoars (n = 36) at Khoo Tech Puat hospital between 2011-2017 was performed. Patient demographics, imaging and operative findings, characteristics of bezoars and related morbidities were analyzed. The study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Treatment of bezoars is dependent on their location within the GI tract. For gastric bezoars, these include chemical dissolution of the bezoar with coca-cola, endoscopic removal or surgery 9 11 12 28. Historically, surgery for gastric bezoars has been via laparotomy,28 however recent literature describes successful laparoscopic surgical techniques to remove gastric bezoars 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of bezoars is dependent on their location within the GI tract. For gastric bezoars, these include chemical dissolution of the bezoar with coca-cola, endoscopic removal or surgery 9 11 12 28. Historically, surgery for gastric bezoars has been via laparotomy,28 however recent literature describes successful laparoscopic surgical techniques to remove gastric bezoars 11…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal bezoars causing obstruction require surgery for removal 9 28 29. Paschos et al describe a case series including four patients, all with SBO from ileal bezoars, who underwent laparotomy and successful removal of bezoar 29.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that those with large volume bezoars (5.3 cm length and 3.7 cm length) and those with higher density bezoars on CT scan were independent risk factors for requiring surgical intervention [ 2 ]. When surgery is needed, the most common operations performed are partial small bowel resection if there is concern for bowel compromise, enterotomy with bezoar extraction, or milking the stone toward the ileocecal valve [ 2 , 10 ]. Furthermore, it is possible to fragment the stone while it remains intraluminal and milk the fragments forward [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the standard treatment for small bowel obstruction due to bezoar (10). Generally, the bezoar is impacted in the narrowest segment of the small bowel, which is at the terminal ileum, just proximal to the ileocecal valve.…”
Section: Discussionmentioning
confidence: 99%